Atrazine and its Use - Pathak R. K.; Dikshit A.K. (International Journal of Research in Chemistry and Environment (IJRCE), 2011)
Atrazine was registered for use in Switzerland in 1956 and in the US in 1958. Aytazine was first released for experiment station evaluations in 1957 and became commercially available in 1958. It quickly became the most popular of the triazines for its effectiveness against a wide spectrum of weeds in a range of conditions, including in dry soil. It has since become one of the most widely researched herbicides to date. It is chlorinated herbicide and most heavily used worldwide. It has been observed that their long-term, low-dose exposure are increasingly linked to human health effects such as immune-suppression, hormone disruption, diminished intelligence, reproductive abnormalities, and cancer. It has been detected in waterbodies. This paper is an attempt to review the use of atrazine worldwide.